Soft Computing in Data Analytics Proceedings of International Conference on SCDA 2018 - Nayak, Janmenjoy; Abraham, Ajith; Krishna, B. Murali; Chandra Sekhar, G. T.; Das, Asit Kumar (Advances in Intelligent Systems and Computing, 2019)
The volume contains original research findings, exchange of ideas and dissemination of innovative, practical development experiences in different fields of soft and advance computing. It provides insights into the International Conference on Soft Computing in Data Analytics (SCDA). It also concentrates on both theory and practices from around the world in all the areas of related disciplines of soft computing. The book provides rapid dissemination of important results in soft computing technologies, a fusion of research in fuzzy logic, evolutionary computations, neural science and neural network systems and chaos theory and chaotic systems, swarm based algorithms, etc. The book aims to cater the postgraduate students and researchers working in the discipline of computer science and engineering along with other engineering branches. .